Buka Siape Sambehin Injin: Komentar Atas Putusan Tentang Izin Lingkungan PLTU Celukan Bawang - Wibisana, Andri Gunawan; Fadhillah, Fajri (UI Scholars Hub, 2022)
This paper examines administrative court’s view in the Izin Lingkungan PLTU Celukan Bawang case. The paper puts emphasis on the use of actual losses to assess the plaintiffs’ legal standing and the deadline for filing a lawsuit. This paper considers that the court was incorrect in interpreting the legal standing by focusing on the absence of plaintiffs’ actual losses. The court also took a conservative position in determining the deadline for filing the lawsuit. This paper criticizes the court’s failure to take into account the issue of climate change addressed by the plaintiffs, so that the court missed a golden opportunity to become one of the few rulings pioneering the discussion of climate change in the EIA study. It is the court's inaccuracy in assessing the interests of the Plaintiffs that prevented the court from seriously and deeply discussing the substantive issues argued by the plaintiffs, including the issue of climate change.